An observational study of buprenorphine treatment of the prescription opioid dependent pain patient. (12th February 2015) - Streltzer, Jon; Davidson, Raymond; Goebert, Deborah
<x xml:space="preserve">Abstract</x> Background and Objectives In some countries, particularly the United States and Canada, there has been a growing problem of opioid dependence associated with the treatment of chronic pain. Controversy exists regarding the efficacy and safety of opioid therapy, particularly in high doses for extended periods of time. This study reports on the outcome of chronic pain patients treated with buprenorphine in an outpatient psychiatric consultation clinic. Methods Forty three consecutive outpatient clinic chronic pain patients with a DSM‐IV diagnosis of opioid dependence and treated with buprenorphine during a 3‐year period were monitored for follow‐up periods of up to 5 years. All subjects were dependent on drugs prescribed for pain and were divided into two groups: those who had a history of abuse of alcohol or drugs and those who did not Historical, physical, demographic, and outcome data were collected. Results The majority of patients were male, not working, and between the ages of 45–60. Follow‐up revealed that treatment with buprenorphine was effective. Most patients had improved pain with treatment of the opioid dependence. There were no differences between those with or without a history of substance abuse. Discussion and Conclusions Patients often improved with much less preoccupation with pain, expressing great satisfaction with buprenorphine treatment. Scientific Significance Buprenorphine is an effective tool when treating the opioid‐dependent chronic pain patient. (Am J Addict 2015;XX:1–5)